Structural and dielectric relaxor properties of Ba1-xMgxTiO3 ceramics prepared through a hydrothermal route. (4th July 2018) - Shandilya, Mamta; Rai, Radheshyam; Zeb, Aurang
ABSTRACT: Polycrystalline samples of lead-free Ba1- x Mg x TiO3 (where x  = 0.05, 0.10, 0.15) have been fabricated by a hydrothermal method. Single-phase perovskite-type X-ray diffraction patterns were observed and samples have a phase with a tetragonal structure at room temperature for all compositions. The SEM image of the powder shows the agglomeration with increment of Mg concentrations. Small grains with average grain sizes of ∼20 ± 5 nm are uniformly distributed over the mesocrystals. TEM specimens show well-dispersed spherical barium magnesium titanate nanoparticles and diameter of these particles is around 270–300 nm. A dielectric study of Ba1- x Mg x TiO3 ceramics as a function of temperature suggested that with increasing substitution concentration the dielectric constant decreased and the Curie temperature shifted towards the lower temperature side. The dielectric diffusivity ( γ ) was found to be maximum (1.86) for substitution of x  = 0.10 in Ba1- x Mg x TiO3 compounds. The activation energy (Ea) was found to increases with increasing substitution concentration in BMT compounds.